ntifungal Activity of the Extracts of Garad (Acacia nilotica L.) - A. M1, Abdel-Rahim; Y. A, Wafa; F. A, Idris, (Gezira Journal of Engineering and Applied Sciences, 2018)
Plants may represent a potential source of antimicrobial compounds as evidenced by the huge studies dealing with antimicrobial activities of medicinal plants. However, Sudan posses an immense wealth of medicinal plants, that is still unexploited. The present study was mainly conducted to investigate the antifungal of the most important and widely distributed Garad tree ( Acacia nilotica L. ) in the country. The extracts of the different parts of the tree were tested against the mycelial growth, mycelial weights and spore germination of two fungi ( Penicillium italicum and Aspergillus niger ). The inhibition zone and the radial growth methods were used for mycelial growth using PDA media. Extraction with different solvents confirmed that, Methanol, Diethyl ether, Acetone and the aqueous extracts were found highly effective in inhibiting growth of both fungi. The results also showed that the different tree parts had different effects with the extracts of both the tree bark and pods as the best effective. It is also clear that the extracts reduced both fresh and dry weights of mycelia of the two fungi. However, A. niger was found more sensitive to the extracts compared to P. italicum . The extracts reduced germination effectively, where only 23% and 37.7% of the spores of A. niger and P. italicum germinated, respectively, at the higher concentration of the extract (100mg/ml). It could be concluded that the extracts of Garad are highly effective as antifungal agents, specially the bark and pods of the tree. It could be recommended that the test should be carried on other microorganisms.